Cherry blossoms after winter 2 - Bamwoo (Bamwoo. Cherry blossoms after winter, 2025)
Seo Haebom had only just gotten used to having his friend-turn-distant-housemate, Jo Taesung, acknowledge his existence, but now it seems like they might actually be...friends again? As Taesung brings Haebom into his social circle, Haebom discovers not only how much he's missed his childhood playmate, but how much more fun high school can be if he has the confidence to stop being such a wallflower. But after so many years of a predictable-if lonely-life, Haebom now can't seem to stop his world from changing too quickly. Just as he begins to enjoy his new normal, Taesung starts acting like he might want to change their relationship yet again, this time to something more than friends.--